2010
DOI: 10.1002/jctb.2342
|View full text |Cite
|
Sign up to set email alerts
|

Supported photocatalysis as a pre‐treatment prior to biological degradation for the removal of some dyes from aqueous solutions; Acid Red 183, Biebrich Scarlet, Methyl Red Sodium Salt, Orange II

Abstract: International audienceBACKGROUND: The aim of this study was to assess the feasibility of coupling photocatalysis and a biological treatment for the removal of azo dyes from aqueous effluents. Biological processes do not always appear relevant for dyes removal, owing to the low or total absence of biodegradability of this class of pollutants. RESULTS: During photocatalysis pre-treatment, a decrease in the chemical oxygen demand (COD) indicated oxidation of the target compound and thus a change in the chemical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 55 publications
4
23
0
Order By: Relevance
“…Similar observations were reported for the degradation of dyes [141], cyproconazole [142], and a tetracycline/tylosin mixture [143], in which the TiO 2 photocatalytic pre-treatment eradicated the activity of biological oxidation. In this case, some of the intermediates generated during photocatalysis were not biodegradable.…”
Section: Coupling With Other Treatment Technologiessupporting
confidence: 82%
See 1 more Smart Citation
“…Similar observations were reported for the degradation of dyes [141], cyproconazole [142], and a tetracycline/tylosin mixture [143], in which the TiO 2 photocatalytic pre-treatment eradicated the activity of biological oxidation. In this case, some of the intermediates generated during photocatalysis were not biodegradable.…”
Section: Coupling With Other Treatment Technologiessupporting
confidence: 82%
“…These technologies include electrocatalysis [35,[136][137][138], sonocatalysis/Fenton process [139], biodegradation [140][141][142][143][144], and wetland technology [145]. The combination of NTO photocatalysis with any of these techniques can not only improve the total efficiency of the degradation but also has the advantage of treating large quantities of wastewater (in real systems), especially with electrocatalysis, biodegradation, and wetland technology.…”
Section: Coupling With Other Treatment Technologiesmentioning
confidence: 99%
“…In such integration, the advanced oxidation process (AOP) constitutes a pretreatment in order to increase the biodegradability of the effluent degrading recalcitrant pollutants and/or to reduce toxicity [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the most widely physicochemical treatments studied are photo-Fenton and photocatalytic ones. Previous works indicated that the considered integrated process did not seem to be relevant to treat the pesticide cyproconazole [23] and some azo dyes [18], and its use appeared limited in the treatment of antibiotic wastewater (57 % chemical oxygen demand (COD) removal) [24]. In contrast, photocatalytic degradation of sulfamethoxazole resulted in an increase of biodegradability [25], and an integrated photocatalytic-biological reactor led to 92 % mineralization during phenol degradation [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation